THE CORRELATION BETWEEN TRANSLATING ABILITY AND SPEAKING ABILITY - Farida, Risa; Rahayu, Kartika Sri (PROJECT (Professional Journal of English Education), 2018)
English is a foreign language that is learned by students in indonesia from elementary school until senior high school to make them able to communicate with all people around the world. One of four major skill is Speaking, if we have mastered the language we show it by our speaking skill to communicate with the other. In the other side there is also other important ability, that is translating ability. Translating ability play a role when learning the four major skills, in this case the role when learning speaking skill. Therefore, the main objective of this study to reveal the correlation between translating ability and speaking ability. The research method used is quantitative research, or more specifically the correlation design which consists of 35 students as the sample and oral and essay test as the instruments. For calculating the data, the writer used SPSS using Pearson Product Moment to know the correlation from two variables. The writer find the result of the data is r = 0.414. based on the result found that there is a moderate correlation between translating ability and speaking ability. Keywords:  Correlation, Translating ability, Speaking ability